Eucypris fontana (Graf, 1931) (Crustacea, Ostracoda) in permanent environments of Patagonia Argentina: A geometric morphometric approach - Ramos, L. Y. (2015)
Ostracods are microcrustaceans with a calcareous carapace, very useful as paleoenvironmental indicators. Eucypris fontana (Graf, 1931) is a non-marine ostracod species, distributed in southern Neotropics, commonly found in living bisexual populations as well as in quaternary sequences in Patagonia. Geometry morphometric analysis offers efficient and powerful techniques to quantify, describe and analyze shape and size variations. In this study, phenotypic changes in the carapace (size and shape) of E. fontana were analyzed using geometric morphometric methods. One hundred and two valves, including males and females from surface sediments of six permanent water bodies located in Patagonia, Argentina, were analyzed. Male and female valves are spread in the morphospace and sexual dimorphism in size and shape were no perceived. Valve size (centroid size) differed between environments; larger individual were correlated with higher Mg2+, Ca2+, K+ concentrations and temperature and lower pH (~9.1) of the host waters, whereas smaller specimens were associated with the opposite environmental extreme. The principal component analysis performed with Procrustes coordinates (shape) indicated a morphological gradient between elongated and rounded valves; major changes occurring on the dorsal margin, calcified inner lamella and in the position of the adductor muscles scars. Rounded carapaces were related whit higher Ca2+ and Mg2+ concentration and lower pH (~8.6) environments, whereas elongated valves were associated with the opposite environmental extreme. These results highlight the importance of morphometric studies of E. fontana in ecological research and their potential use in paleoenvironmental studies in Patagonia and other regions where this taxon is found.